Factors Effected the Performance of Green Building in Madrasah Building Components - Sedayu, Agung (Proceeding International Conference on Science and Engineering, 2019)
Educational institutions in the form of madrasah have been growing rapidly in Indonesia. The madrasah is maneged by government and private institutions. This shows that public trust to madrasah as a place of spiritual and academic learning is increasing. Madrasah are supported by several building facilities in achieving the success of their learning activities. This study aims to determine the factors that influence the performance of green building in the Madrasah Al-Rifaie. A review of the determination of performance factors is green building with a background that green building for the present is a solution to the realization of buildings that do not damage the environment. The research results obtained 10 performance factors including Security, Safety and Healthy, Facilities Function, Aesthetics, Easiness and Accessibility, Reliability, Durability, Comfortable and Regularity, Availability and Capacity, and Environmentally-friendly. The average of the important level of 10 performance factors are in important scale (scale 4). The results of this analysis can be continued at the stage of data collection and further analysis.